Analisis Keselamatan Pasien di Rumah Sakit Berdasarkan Pendekatan Beban Kerja dan Komunikasi - Hendry Wibowo; Inayah Putri Andini (Journal of Innovative and Creativity, 2025)
In 2025, Bungo Hospital saw a 0.3% rise in patient safety issues. If left unchecked, these issues may damage hospitals' and patients' reputations. Poor communication and a heavy workload are the causes of an error that arises and contributes to an increase in patient safety occurrences. This study set out to examine how communication and workload affected the frequency of patient safety incidents in hospitals. There are eighteen work units that directly serve patients in this study's unit analysis. There were 90 participants in total, including the head of the work units, the person in charge of the work units, and the person in charge of the work units' quality. Google Forms questionnaire instruments were used to gather the primary data. The Workload Indicator of Staffing Needed (WISN) computation is used to quantify workload, and the Communication Openness Measurement (COM) is used to measure communication. The patient safety committee provided the data on patient safety incidents. Cross tabulation was used for the analysis, and the Pareto principle was used for interpretation. The findings indicated that 33.3% of work units had a high patient safety incident rate, the majority of work units (83.3%) had a low workload, and the majority of work units (61.1%) had poor communication. The Pareto concept revealed that while communication affected the number of patient safety incidents, workload had no effect on patient safety occurrences. Therefore, in order to improve information flow, knowledge transfer, and employee comprehension of the significance of patient safety in hospitals, hospitals must improve communication patterns and flows as well as the requirement for information disclosure.